Child Trafficking and India With Special Reference to Commercial Sexual Exploitation of Children (CSEC) - Dutta, Devaraj (International Journal of Psychosocial Rehabilitation, 2020)
In today’s world trafficking of children has become a matter of serious concern for all. Every year a large number of children are trafficked throughout the world for a range of purposes such as commercial sexual exploitation, child labour, child marriage, begging, illegal adoption, and so on. In India too the problem of child trafficking is assuming a very serious form day by day. “India for long has been considered the source, destination and transit country for women and children for forced labour and sex-trafficking” (HAQ, 2016, P. 10). In the light of this, the present study is an attempt to discuss about the issues of child trafficking and Commercial Sexual Exploitation of Children (CSEC) in the context of India. Besides focusing on various causes and magnitude of the problem, the paper also discusses about the impact of human trafficking on children. In conclusion the paper suggests that for effective prevention it is imperative to understand the root causes of the problem as well as to find out solutions so that the risk can be minimised. Careful and in-depth research is required to know about the connection between child trafficking and other child protection issues. Further, ensuring children’s active participation and paying attention to their experiences and recommendations to combat trafficking at all levels of decision-making is also very crucial.